Consumer Acceptance of Pesticide-Free Dairy Products in Germany: A Partial Least Square Model - Marie-Catherine Wendt; Ramona Weinrich (German Journal of Agricultural Economics (GJAE), 2024)
A key challenge in this century is to ensure safe food for a growing global population while limiting environmental impacts and addressing climate change. Although pesticides ensure high yields, there are downsides to their intensive use, including negative effects on the environment, such as water, soil, and air contamination, as well as on biodiversity. To promote a sustainability transition, innovative farming systems that do not require the use of pesticides yet are non-organic can be part of the solution. To explore the attitudes toward a pesticide-free, but non-organic farming system, we examined attitudes and factors that drive German consumers to accept pesticide-free food products, using an online questionnaire to survey 1,010 German consumers. A range of hypotheses were evaluated to determine the factors that influence consumer decisions. Partial least squares structural equation modelling (PLS-SEM) served to assess consumer attitudes and acceptance of pesticide-free milk, butter, and cheese. The study results show that attitudes and acceptance for pesticide-free food products are driven by health consciousness, chemophobia, and perceived consumer effectiveness; they are inhibited by price sensitivity. We find attitudes towards pesticide-free food products to positively moderate the effect of health consciousness, while chemophobic attitudes and perceived consumer effectiveness positively moderate acceptance of pesticide-free food products. Our findings can support researchers, food industry professionals, and regulatory leaders seeking scalable pesticide-free agricultural production methods.
Keywords: 330; Consumer Acceptance; Structural Equation Modelling; Pesticide-Free Farming; Pesticide Residues